Using the Team to Reduce Risk of Blood and Body Fluid Exposure in the Perioperative Setting - Moore, Carolyn; Edward, Karen-leigh; King, Karolin; Giandinoto, Jo-Ann (Operating Room Nurses Association of Canada Journal, 2015)
Introduction: Despite the substantial risks posed in the surgical environment, compliance in wearing appropriate personal protective equipment (PPE) in the operating room (OR) and the postanaesthetic care unit (PACU) amongst health care workers is considered poor globally. Lack of awareness and limited access to information about the appropriate precautions to prevent exposure contribute to continued highrisk behaviours amongst the team in the perioperative setting. Aim: The aim of this project was to assess current compliance rates of staff in the use of PPE and to develop and implement an educational program to increase staff compliance in the perioperative setting of a large, private hospital (450 beds). Method: A convenience sample of perioperative nurses were invited to complete a questionnaire. Results: Eighty (80) registered nurses (RNs) were invited to participate (response rate of 69%), giving a sample size of n=55. Questionnaires not completed in full were not included in the final analysis, leaving n=31 fully completed questionnaires. There was an education group (n=14) and a control group (n=17). Between the groups, educational background, type of work and patient contact were very similar. Of those that did respond regarding exposure, only 20% reported the incident. Both groups identified their manager and team as frequently discussing safer work practices and being supportive. PPE was identified as essential; however, participants reported not enough time to always follow standard precautions (education 15%; control 25%). Conclusions: Team and good leadership was identified as essential to ongoing professional knowledge and support with regard to risk minimisation in the perioperative setting.